Enhancing the perception of a student-friendly institution through the green environment: Insights from a Hungarian university - Gabriella Horváth-Csikós; Tímea Juhász (Knowledge & Performance Management)
This paper explores the concept of place attachment, encompassing its meaning and representation among university students. It provides a comprehensive picture of place identity and place attachment among university students. The planned approach was to conduct a survey among students to examine their attachment to place from a green perspective. A questionnaire was used, and the data were analyzed using SPSS version 28 and Smart PLS 4. This paper summarizes the results of a survey of 245 students studying at the Budapest University of Economics and Business in 2022/23. The students were graduates in International Studies and Commerce-Marketing. The setting of the study was the university environment because it is an institution of higher education, a bastion of knowledge transfer, and the issue of attachment is very important in the relationship between educational institutions and students. The results confirmed that students perceived green energy (β: 0.283, t: 4.637 p: 0.000) and green solutions (β: 0.430, t: 9.155 p: 0.000) as having a significant effect on whether or not they perceived the institution as student-friendly. It is no coincidence, therefore, that students are satisfied with the green environment of the university (74%). They believe that the university has an adequate amount of green space (68%). However, the current situation could be improved, with a large proportion of students missing the widespread use of green (79%) and renewable energy (70%) in the institution.